PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS VIDEO TUTORIAL PEMBUATAN TUSUK DASAR HIAS KELAS XI DI SMK SOSIAL SOSIAL ISLAM 1 PRAMBANAN TAHUN PELAJARAN 2022/2023 - Navila, Bunga (Universitas Sarjanawiyata Tamansiswa, 2024)
This study aims to find out: 1) the steps for developing learning videos for making decorative basic skewers, 2) the feasibility of learning media from the development results, and 3) the response of students to the learning media developed. This research method is research and development (R&D) with a four-D model. The validators of this research consist of material experts and media experts, as well as class XI learners as subjects. The object of this research is the development of video tutorial learning media. The instrument used is a questionnaire. Data analysis techniques use quantitative descriptive analysis. This research produces video tutorial learning media for making various ornamental basic skewers that are suitable for use. The assessment obtained from media experts and material experts gets a percentage of 100%. The results of small-scale student trials scored 92.70% and large-scale trials scored 85%. The value of the results of small-scale trials and large-scale trials falls into the category of strongly agree.